2011
DOI: 10.1063/1.3587122
|View full text |Cite
|
Sign up to set email alerts
|

Multi-beam effects on backscatter and its saturation in experiments with conditions relevant to ignition

Abstract: To optimize the coupling to indirect drive targets in the National Ignition Campaign (NIC) at the National Ignition Facility [E. Moses et al., Phys. Plasmas 16, 041006 (2009)], a model of stimulated scattering produced by multiple laser beams is used. The model has shown that scatter of the 351 nm beams can be significantly enhanced over single beam predictions in ignition relevant targets by the interaction of the multiple crossing beams with a millimeter scale length, 2.5 keV, 0.02−0.05 × critical density, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
4
30
1
Order By: Relevance
“…In this geometry the sharing of ion waves cannot produce amplification of the seed beam as has been observed in other geometries [18]. This demonstration is the basis for an emerging model of the effect of multibeam amplification of scatter on the coupling in ignition targets [22,23].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In this geometry the sharing of ion waves cannot produce amplification of the seed beam as has been observed in other geometries [18]. This demonstration is the basis for an emerging model of the effect of multibeam amplification of scatter on the coupling in ignition targets [22,23].…”
supporting
confidence: 57%
“…The ion waves produced by crossing laser beams may also be important because their effect on stimulated Raman scatter (SRS) has been documented [21]. Most recently, an analysis of the effect of the multiple pump beams intersecting the light backscattered from the interior of ignition targets has shown that, even when the linear gain exponent of each pump beam is 1, the combined effect of up to 23 crossing pumps can amplify both Brillouin and Raman scatter by 10 to 100 fold if the waves remain linear [22,23] and if the individual pumps can all amplify the same light wave.…”
mentioning
confidence: 99%
“…In terms of the characteristic size of the speckles, the simulation region is 24 speckle widths and 3.5 speckle lengths (85 speckles total). These laser and plasma conditions are similar to those obtained in NIF ignition targets near the end of the laser pulse when SRS reflectivity is highest [10]. The reflectivity, shown in the upper left of Fig.…”
supporting
confidence: 63%
“…SBS phase conjugation is appropriate for combining beams from an amplifier array (Bowers, 1997). Research continues on how to combine the many beams needed for laser fusion (Kirkwood, 2011).…”
Section: Applications Of Stimulated Brillouin Scatteringmentioning
confidence: 99%